Immunoterhapy in Pancreatic Cancer - Dalkılıç, Semih; Dalkılıç, Lütfiye Kadıoğlu; Uygur, Lütfü (Bolu Abant İzzet Baysal Üniversitesi, 2025)
Cancer is a complex and deadly group of diseases that seriously affects individuals' quality of life. Among these diseases, pancreatic cancer stands out due to its aggressive course, late diagnosis, and low response rate to current treatments. The immunosuppressive tumor microenvironment of pancreatic adenocarcinoma, its low immunogenicity, and its dense stromal component play a significant role in the development of treatment resistance. Currently, standard treatment methods such as surgery, chemotherapy, and radiotherapy provide limited success; therefore, there is a need for new treatment approaches such as immunotherapy. Immunotherapy is a rapidly developing treatment method that aims to activate the immune system and create a specific and long-lasting response against tumor cells. However, the effectiveness of immunotherapy in pancreatic cancer is quite low compared to other types of cancer. This situation stems from the decrease in immune cell infiltration in the tumor microenvironment and the effectiveness of immune escape mechanisms. Recent studies have shown that combining immunotherapies with chemotherapy or radiotherapy may yield more effective results. The aim of this review is to evaluate the current status of immunotherapeutic approaches in pancreatic cancer, the biological and clinical challenges encountered, and current strategies to improve treatment efficacy in light of the literature. Additionally, new-generation treatment combinations and ongoing clinical trials that may guide future clinical applications will also be discussed.

Kanser, bireylerin yaşam kalitesini ciddi şekilde etkileyen, kompleks ve ölümcül bir hastalık grubudur. Bu hastalıklar arasında pankreas kanseri, agresif seyri, geç evrede tanı alması ve mevcut tedavilere düşük yanıt oranı ile dikkat çekmektedir. Pankreatik adenokarsinomun immün baskılayıcı tümör mikroçevresi, düşük immünojenik yapısı ve yoğun stromal komponenti, tedaviye direnç gelişiminde önemli rol oynamaktadır. Günümüzde cerrahi, kemoterapi ve radyoterapi gibi standart tedavi yöntemleri sınırlı başarı sağlamakta; bu nedenle immünoterapi gibi yeni tedavi yaklaşımlarına ihtiyaç duyulmaktadır. İmmünoterapi, bağışıklık sistemini aktive ederek tümör hücrelerine karşı spesifik ve uzun süreli bir yanıt oluşturmayı amaçlayan, hızla gelişen bir tedavi yöntemidir. Ancak pankreas kanserinde immünoterapinin etkinliği, diğer kanser türlerine kıyasla oldukça düşüktür. Bu durum, tümör mikroçevresinde immün hücre infiltrasyonunun azalması ve immün kaçış mekanizmalarının etkinliğinden kaynaklanmaktadır. Son yıllarda yapılan araştırmalar, immünoterapilerin kemoterapi veya radyoterapi ile kombinasyonunun daha etkili sonuçlar verebileceğini göstermektedir. Bu derlemenin amacı, pankreas kanserinde immünoterapötik yaklaşımların mevcut durumunu, karşılaşılan biyolojik ve klinik zorlukları ve tedavi etkinliğini artırmaya yönelik güncel stratejileri literatür ışığında değerlendirmektir. Ayrıca, gelecekteki klinik uygulamalara yön verebilecek yeni nesil tedavi kombinasyonlarına ve devam eden klinik çalışmalara da yer verilecektir.
Pankreas Kanserinde İmmünoterapi
Keywords: Pharmaceutical Biotechnology; Farmasotik Biyoteknoloji; Cellular Immunology; Hücresel İmmünoloji